Repetitions in reserve vs. maximum effort resistance training programs in youth female athletes - Arede, J.; Vaz, R.; Gonzalo-Skok, O.; Balsalobre-Fernandéz, C.; Varela-Olalla, D.; Madruga-Parera, M.; Leite, N. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: This study aimed to analyze and compare the effects of two different resistance training programs. METHODS: Fourteen under-17 youth female basketball players were randomly assigned to repetitions in reserve (RIR, N.=7) or maximum effort (RM, N.=7) resistance training programs. The programs consisted of 3-4 sets of 4 exercises x 7-10 repetitions with 2 min of passive recovery between sets and exercises, twice a week for a period of 8 weeks. The RIR group was instructed to perform the exercises with 3 repetitions remaining (rate of perceived exertion [RPE] =7). The physical assessment included jumping, agility, and sprinting tests. Moreover, the maximum strength (one maximum-repetition [1-RM]) and muscle power output at 60% 1RM were assessed for back-squat and bench-press exercises. RESULTS: The within-group analysis showed improvements in all tests for both groups (RIR=1.3-43.9%; RM=1.3-17.2%). Between-group analyses showed a significant interaction effect (group x time) on 1-RM bench-press (F=8.07, P<0.05, ?2p=0.40), favoring RIR group. CONCLUSIONS: This study reports for the first time that the use of RIR-based RPE resistance training protocol promotes improvements in high-intensity actions (sprinting, jumping, and cutting), muscle power output, and maximum strength, particularly in youth athletes. Considering the advantages of non-failure training, RIR training may be a suitable in-season training strategy. However, more studies are needed to confirm whether the training-induced benefits of this novel training strategy are significantly better as compared to other approaches.